Contemporary outcomes of cardiac surgery patients supported by the intra-aortic balloon pump. (5th April 2022) - Lorusso, Roberto; Heuts, Samuel; Jiritano, Federica; Scrofani, Roberto; Antona, Carlo; Actis Dato, Guglielmo; Centofanti, Paolo; Ferrarese, Sandro; Matteucci, Matteo; Miceli, Antonio; Glauber, Mattia; Vizzardi, Enrico; et al.
Abstract: OBJECTIVES: Although the intra-aortic balloon pump (IABP) has been the most widely adopted temporary mechanical support device in cardiac surgical patients, its use has declined. The current study aimed to evaluate the occurrence and predictors of early mortality and complication rates in contemporary cardiac surgery patients supported by an IABP. METHODS: A multicentre, retrospective analysis was performed of all consecutive cardiac surgical patients receiving perioperative balloon pump support in 8 centres between January 2010 to December 2019. The primary outcome was early mortality, and secondary outcomes were balloon-associated complications. A multivariable binary logistic regression model was applied to evaluate predictors of the primary outcome. RESULTS: The study cohort consisted of 2615 consecutive patients. The median age was 68 years [25th percentile 61, 75th percentile 75 years], with the majority being male (76.9%), and a mean calculated 30-day mortality risk of 10.0%. Early mortality was 12.7% ( n = 333), due to cardiac causes ( n = 266), neurological causes (=22), balloon-related causes ( n = 5) and other causes ( n = 40). A composite end point of all vascular complications occurred in 7.2% of patients, and leg ischaemia was observed in 1.3% of patients. The most important predictors of early mortality were peripheral vascular disease [odds ratio (OR) 1.63], postoperative dialysis requirement (OR 10.40) and vascular complications (OR 2.57). CONCLUSIONS: The use of the perioperative IABP proved to be safe and demonstrated relatively low complication rates, particularly for leg ischaemia. As such, we believe that specialists should not be held back to use this widely available treatment in high-risk cardiac surgical patients when indicated. Abstract : The intra-aortic balloon pump (IABP) has traditionally been the most widely adopted temporary mechanical circulatory support device in cardiac surgical patients [1] and is particularly applied in patients undergoing coronary artery bypass grafting (CABG) because of its effects on coronary blood flow and reduced left ventricular (LV) end-diastolic pressure [2].